An Instrument for the Determination of a Hydropneumograph in a Bubbling Spring. Issue 2 (3rd June 2019) - Agnew, Robert J.; Halihan, Todd; Holtzhower, Lantz; Norton, Brian
Abstract: In order to enable greater accuracy in the determination of the mass discharge of gas and water‐gas ratios (WGR) in groundwater from springs, we have developed a field‐deployable instrument using commercially available components to independently measure the gas and water mass flow rates in springs with bubbling mixed‐phase flow. Collecting and measuring the free gas phase will allow for further compositional analysis that may be useful in improving gas‐derived parameters such as recharge temperature and age, as well as quantification of methanogenesis and flux of crustal/mantle gasses. By installing a phase separator at the spring discharge, a thermal mass flow sensor is utilized to measure the gas flow rate (ebullition + flux) generated from a spring. The water flow rate is determined by a standard weir. Field performance of the device was tested on a spring discharging from the Arbuckle‐Simpson aquifer near the town of Connerville in south‐central Oklahoma, USA. Abstract : Article impact statement : Instrument for accurate measurement of gas and water mass flow rates from bubbling springs is described.